Working together to support new environments for learning.Working with staff to support innovation. - Hudson, Alison (REBIUN, 2003)
Provide an overview of the impact of elearning across the University Describe current models of support, new roles and relationships-focus on Multimedia Courseware Developers. Illustrate a range of innovative teaching and learning developments Consider the implications for staff
Keywords: Centros de Recursos para el Aprendizaje y la Investigación (CRAI); Edificios y espacios bibliotecarios; Servicios de apoyo a la docencia